2020
DOI: 10.3389/fmicb.2020.02039
|View full text |Cite
|
Sign up to set email alerts
|

Weissella cibaria Attenuated LPS-Induced Dysfunction of Intestinal Epithelial Barrier in a Caco-2 Cell Monolayer Model

Abstract: The dysfunction of the intestinal epithelial barrier contributes to local or systemic infection and inflammation. Some lactic acid bacteria (LAB) strains had been shown to improve the conditions of barrier function and, for this reason, are recognized as probiotics. Weissella cibaria, a species belonging to the LAB group, is known to promote several health benefits. However, the role of W. cibaria in regulating the integrity of the intestinal epithelial barrier has not yet been investigated. In this study, W. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…1,4,5 Although the precise pathogenesis of UC remains controversial, a considerable number of recent studies have shown that the unavoidable pathogenic factors contributing to ulcerative colitis include both the dysfunction of the intestinal epithelial barrier and the excessive release of inflammation and oxidative stress. 6,7 Impairment of the gut barrier contributes to gut leakage, which facilitates the access of lumen stimulators, including bacteria, toxins, and antigens, to the internal organs, resulting in the occurrence and progression of chronic inflammation and abnormal immune responses. 8,9 Thus, exploring a therapeutic or prophylactic approach to restore and maintain the homeostasis of the intestinal barrier may help ameliorate the manifestations of UC.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 Although the precise pathogenesis of UC remains controversial, a considerable number of recent studies have shown that the unavoidable pathogenic factors contributing to ulcerative colitis include both the dysfunction of the intestinal epithelial barrier and the excessive release of inflammation and oxidative stress. 6,7 Impairment of the gut barrier contributes to gut leakage, which facilitates the access of lumen stimulators, including bacteria, toxins, and antigens, to the internal organs, resulting in the occurrence and progression of chronic inflammation and abnormal immune responses. 8,9 Thus, exploring a therapeutic or prophylactic approach to restore and maintain the homeostasis of the intestinal barrier may help ameliorate the manifestations of UC.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial barrier loss dysfunction model in vitro was established using Caco-2 cells (1 × 106) monolayer incubated LPS (0.5 ng/mL) for 3 days [ 26 ]. Caco-2 monolayers were treated with LPS or Shaoyao Decoction medicated serum.…”
Section: Methodsmentioning
confidence: 99%
“…Deoxynivalenol (DON), a secondary metabolite from the fungi in the corns, could easily damage the intestinal barrier (16,17). The human colon cancer cell line Caco-2 grown in the transwell plates was commonly used as an intestinal barrier model to mimic the gut barrier of humans (18)(19)(20). However, this Caco-2 cell monolayer mimicked gut barrier has been questioned due to its characters of rapid growth and malignant proliferation.…”
Section: Introductionmentioning
confidence: 99%